Perspectives on the implementation of screening and treatment for depression and alcohol use disorder in primary care in Colombia (2021)
Depression and alcohol use disorder (AUD) greatly contribute to the burden of disease worldwide, and have large impact on Colombia’s population. In this study, a qualitative analysis evaluates the implementation of a technology-supported model for screening, decision support, and digital therapy for depression and AUD in Colombian primary care clinics. Patient, provider, and administrator interviews were conducted, exploring attitudes towards depression and AUD, attitudes towards technology, and implementation successes and challenges. Researchers used qualitative methods to analyze interview themes. Despite stigma around depression and AUD, the model improved provider capacity to diagnose and manage patients, helped patients feel supported, and provided useful prevalence data for administrators. Challenges included limited provider time and questions about sustainability. The implementation facilitated the identifcation, diagnosis, and care of patients with depression and AUD. There is ongoing need to decrease stigma, create stronger networks of mental health professionals, and transition intervention ownership to the healthcare center